Prolonged Remission of Major Depressive Disorder After Single Nitrous Oxide Inhalation Treatment - Nagele, Peter; Brown, Frank; Bass, Victoria; Yohanna, Daniel (Frontiers in Psychiatry, 2020)
Here, we present a case where a patient with severe recurrent treatment resistant major depression experienced full remission, which lasted more than one month, after a single nitrous oxide inhalation treatment.